Visualization of Corset Transparency Techniques nd Velvet Fabric Textures in the “Viraadhya” Evening Gown Based on the Design Characteristics of Jacob Wil - Aditia Wahyu Kusuma; Glenda Talitha Br Sembiring; Ellizabeth Cecillia L.; Putri Adelaide Rohim; Adhi Kusumastuti (Journal of Creativity Student, 2026)
The development of contemporary fashion has transformed clothing from a functional necessity into a medium of visual expression that embodies both aesthetic and symbolic values. This study aims to analyze the design characteristics of Jacob Wil as reflected in the evening gown “Viraadhya” through the visualization of corset transparency techniques and velvet fabric texture as key elements in shaping the garment’s aesthetic value. The research employs a qualitative approach using a descriptive-analytical method. Data were collected through visual observation, documentation studies, and literature reviews. The analysis focuses on design aesthetics, garment construction, material texture, and fashion semiotics. The findings indicate that “Viraadhya” successfully represents Jacob Wil’s distinctive design  characteristics through the application of a structured mermaid silhouette, the exploration of transparent corset construction, and the combination of velvet and transparent materials that create a visual contrast between strength and softness. The corset transparency technique functions not only as a constructive element but also as an aesthetic strategy that reinforces the garment’s visual identity. Meanwhile, the use of velvet fabric contributes a sense of luxury, drama, and visual depth that supports the overall design narrative. This study demonstrates that the exploration of garment construction and material innovation can serve as an important strategy in establishing visual identity within contemporary evening gown design.  Keywords: Corset transparency, velvet fabric, evening gown, Jacob Wil, fashion Design.